Évaluer, inventorier, exploiter : le Rotulus de denariis de l’abbaye Saint-Étienne de Caen (XIIIe siècle) - Thomas Jarry (Tabularia)
The Archives départementales of Calvados possess, amongst the collection of the former abbey of Sain-Etienne at Caen, a roll of damaged parchment of which the contents date back to the early thirteenth century. The document lists a number of services and tolls collected by the abbey from its possessions on the plains surrounding Caen. They are classified on a geographical basis as shown here; several of the abbey’s vavasors are mentioned by name. The memorandum, which is of a type similar to the rentals known from the same period, reveals a shift in the economic infrastructure, more in particular it reveals the move towards payment in cash.